Analytical model to determine the relevant parameters governing the transferred momentum to spherical indenters by laser-induced shock waves. (October 2021) - Valentino, Tobias
Highlights: A novel indentation method based on laser-induced shock waves is introduced and described. An analytical model is derived to determine the transferred impulse to spherical indenters. Schlieren method and pendulum tests are performed to validate the model. Fundamental relationships are determined regarding the available forming energy. The model enables the targeted design of laser-based shock wave processes. Abstract: Rapid material development is a new approach to reduce the time and cost intensity. It is based on small and simple sample geometries. Many conventional test methods such as hardness measurements or tensile tests are not suitable for this approach, because they either require a sample geometry adapted to the test method or they are time-consuming. Thus, research is being conducted on a novel impact-based method, which allows short time indentations and correlations with mechanical material properties such as hardness and tensile strength: With a high intensity pulsed TEA-CO2 laser, a shock wave is generated on top of a spherical indenter. The momentum of the shock wave pushes the indenter inside a sample. From the induced indentations, characteristic values such as indentation depth and indentation diameter are extracted, which correlate well with the material hardness and tensile strength. Still, the process dynamics are not fully understood. Thus, a model is developed to determine the main parameters that govern the interaction between laser-induced shock wave as well as indenter and accordingly, significantly affect the forming energy. The model is validated by experimental results. From the findings of the analytical model and the conducted experiments, fundamental correlations with respect to the available forming energy are determined. The main parameters influencing the available forming energy are pulse energy, pulse duration, laser spot area, density of the ambient medium and indenter mass.